Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Hafalan Al-Qur’an Siswa Kelas VIII di SMP Unismuh Makassar - Feby Nur Anggriani; Abdul Aziz Muslimin; Muh. Khaidir lutfi (Yayasan Al-Afif, 2025)
This study aims to (1) describe the strategies of Islamic Religious Education (PAI) teachers in improving Qur’an memorization among eighth-grade students at SMP Unismuh Makassar, (2) explain the forms of these strategies applied by PAI teachers, and (3) identify the obstacles faced in implementing the strategies to enhance students’ Qur’an memorization. The research employs a descriptive qualitative method with data collected through observation, documentation, and interviews with the principal and Islamic Religious Education teachers at SMP Unismuh Makassar. The findings show that (1) the strategies used by PAI teachers to improve students’ Qur’an memorization include muroja’ah (repetition) and providing guidance to encourage students to be diligent in memorizing. (2) Students’ discipline in maintaining their memorization is implemented by reciting and submitting their memorization after Dhuhr prayer to ensure they consistently review what they have learned. (3) The main obstacle faced by teachers is students’ lack of diligence and consistency in memorizing the Qur’an, which makes it difficult for teachers to overcome these challenges effectively.